New insight into Alzheimer's disease: Light reverses Aβ‐obstructed interstitial fluid flow and ameliorates memory decline in APP/PS1 mice. Issue 1 (1st January 2019) - Yue, Xiangpei; Mei, Yufei; Zhang, Yun; Tong, Zheng; Cui, Dehua; Yang, Jun; Wang, Aibo; Wang, Rui; Fei, Xuechao; Ai, Li; Di, Yalan; Luo, Hongjun; et al.
Abstract: Introduction: Pharmacological therapies to treat Alzheimer's disease (AD) targeting "Aβ" have failed for over 100 years. Low levels of laser light can disassemble Aβ. In this study, we investigated the mechanisms that Aβ‐blocked extracellular space (ECS) induces memory disorders in APP/PS1 transgenic mice and addressed whether red light (RL) at 630 nm rescues cognitive decline by reducing Aβ‐disturbed flow of interstitial fluid (ISF). Methods: We compared the heating effects on the brains of rats illuminated with laser light at 630, 680, and 810 nm for 40 minutes, respectively. Then, a light‐emitting diode with red light at 630 nm (LED‐RL) was selected to illuminate AD mice. The changes in the structure of ECS in the cortex were examined by fluorescent double labeling. The volumes of ECS and flow speed of ISF were quantified by magnetic resonance imaging. Spatial memory behaviors in mice were evaluated by the Morris water maze. Then, the brains were sampled for biochemical analysis. Results: RL at 630 nm had the least heating effects than other wavelengths associated with 49% penetration ratio into the brains. For the molecular mechanisms, Aβ could induce formaldehyde (FA) accumulation by inactivating FA dehydrogenase. Unexpectedly, in turn, FA accelerated Aβ deposition in the ECS. However, LED‐RL treatment not only directly destroyed Aβ assembly in vitro and in vivo but also activated FA dehydrogenase to degrade FA and attenuated FA‐facilitated Aβ aggregation. Subsequently, LED‐RL markedly smashed Aβ deposition in the ECS, recovered the flow of ISF, and rescued cognitive functions in AD mice. Discussion: Aβ‐obstructed ISF flow is the direct reason for the failure of the developed medicine delivery from superficial into the deep brain in the treatment of AD. The phototherapy of LED‐RL improves memory by reducing Aβ‐blocked ECS and suggests that it is a promising noninvasive approach to treat AD. Graphical abstract: Highlights: Aβ‐inactivated formaldehyde dehydrogenase induces formaldehyde accumulation. Formaldehyde in turn accelerates Aβ deposition in the extracellular space. Red light activates formaldehyde dehydrogenase to degrade formaldehyde. Red light reduces Aβ self‐aggregation and formaldehyde‐promoted assembly. Red light recovers interstitial fluid flow and alleviates memory deficits.